The effect of transcutaneous vagus nerve stimulation on pain perception: an experimental study - Busch, Volker; Zeman, Florian; Heckel, Andreas; Menne, Felix; Ellrich, Jens; Eichhammer, Peter (Brain stimulation, 2013)
Background - Recent preclinical work strongly suggests that vagus nerve stimulation efficiently modulates nociception and pain processing in humans. Most recently, a medical device has offered a transcutaneous electrical stimulation of the auricular branch of the vagus nerve (t-VNS) without any surgery. - Objective - Our study investigates whether t-VNS may have the potential to alter pain processing using a controlled design. - Methods - Different submodalities of the somatosensory system were assessed with quantitative sensory testing (QST) including a tonic heat pain paradigm in 48 healthy volunteers. Each subject participated in two experimental sessions with active t-VNS (stimulation) or sham t-VNS (no stimulation) on different days in a randomized order (crossed-over). One session consisted of two QST measurements on the ipsi- and contralateral hand, each before and during 1 h of a continuous t-VNS on the left ear using rectangular pulses (250 μS, 25 Hz). - Results - We found an increase of mechanical and pressure pain threshold and a reduction of mechanical pain sensitivity. Moreover, active t-VNS significantly reduced pain ratings during sustained application of painful heat for 5 min compared to sham condition. No relevant alterations of cardiac or breathing activity or clinical relevant side effects were observed during t-VNS. - Conclusions - Our findings of a reduced sensitivity of mechanically evoked pain and an inhibition of temporal summation of noxious tonic heat in healthy volunteers may pave the way for future studies on patients with chronic pain addressing the potential analgesic effects of t-VNS under clinical conditions.